(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
The article describes the history of Islamic banks, their emergence and evolution, and discusses the differences between traditional banks and Islamic banks. It also suggests reasons why the demand for Islamic banks now tends to increase from year to year.